2022
DOI: 10.1183/13993003.00440-2022
|View full text |Cite
|
Sign up to set email alerts
|

Planetary respiratory health for asthma, rhinoconjunctivitis and eczema

Abstract: More descriptive and analytical epidemiology on asthma, hay fever and eczema are welcome https://bit.ly/3ISD1RQ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is reported that bronchial asthma remains the most common noncommunicable lung disease, the prevalence of which is the highest in middle-and low-income countries [75][76][77][78][79]. The danger of this disease is increased during an asthma attack, which, due to the narrowing of the bronchial lumen, significantly impairs lung ventilation and therefore causes the development of hypoxia [80,82].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that bronchial asthma remains the most common noncommunicable lung disease, the prevalence of which is the highest in middle-and low-income countries [75][76][77][78][79]. The danger of this disease is increased during an asthma attack, which, due to the narrowing of the bronchial lumen, significantly impairs lung ventilation and therefore causes the development of hypoxia [80,82].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that in those countries in which patients are provided with the necessary amount of ICSs and where asthma is treated with standard course doses of IСSs, asthma mortality is lower than in countries in which patients are not fully provided with ICSs [77,[88][89][90][91]. It has been shown that the current standard treatment of asthma with ICSs is not available in countries in which basic inhaled medications containing ICSs are not available to many patients because of their high cost [75,88]. At the same time, the cost of basic inhaled medications containing corticosteroids is still not decreasing [92][93][94][95].…”
Section: Resultsmentioning
confidence: 99%
“…However, none of these associations were sufficient to fully elucidate the relationship between the identified proteins and asthma. The results showed the associations between SNP and multiple allergic diseases and the co-occurrence of asthma and allergic rhinitis ( 35 ), eczema ( 36 ), and atopic dermatitis ( 37 ). This suggests that the aforementioned diseases may share a common etiology.…”
Section: Discussionmentioning
confidence: 99%